Development of an anthropometry-based ergonomic automatic bike design for children with cerebral palsy - Nilma Zola; Annisa Annisa; Dally Rahman (Global Econedu, 2026)
This study aimed to develop an anthropometry-based ergonomic Automatic Bike design tailored to user characteristics. The study employed a Design and Development Research (DDR) approach. The participants consisted of three wheelchair-using children with cerebral palsy at the Rumah Gadang Cerebral Palsy Foundation in Padang, Indonesia. Data were collected through observation, interviews, documentation, anthropometric measurements, and expert validation. Anthropometric data were used as the basis for determining the dimensions and configuration of the Automatic Bike design. The results produced an ergonomic Automatic Bike design with the following specifications: 90 cm overall height, 40 cm width, 50 cm length, 90 cm hand-pedal height, 25 cm foot-pedal height adjustable up to 50 cm, and a 65 cm distance between hand and foot pedals. Expert validation results showed an average score of 2.88 from the engineering expert and 2.70 from the special education expert on a 3-point scale. The overall validation score was 2.79, categorized as highly feasible. These findings indicate that the ergonomic Automatic Bike design meets the requirements of safety, comfort, and suitability for children with cerebral palsy and is appropriate for further prototype development